Sustainable Leadership Model as a Solution to Seasonal Church Services - Jhonderic Molle (International Forum of Researchers and Lecturers, 2025)
Contemporary church ministry is often trapped in a seasonal pattern, with increased activity only during major events like Christmas and Easter, while stagnating at other times. This phenomenon indicates a fundamental problem in leadership patterns that are not poverty-oriented. This article analyzes the roots of seasonal church ministry through a qualitative-descriptive approach and theological reflection based on Osmer's framework. Literature reviews by Barna, Maxwell, Banks & Ledbetter, as well as the leadership principles of Jesus Christ, show that seasonality is eliminated by reactive leadership that lacks a long-term vision, minimal spiritual training, and a weak ministerial cadre system. As a solution, this article offers a sustainable leadership model that emphasizes a year-round discipleship vision, ministerial training and regeneration, systematic ministry evaluation, and the spiritual example of leaders. This model is believed to help churches experience stable growth, establish a consistent ministry rhythm, and present relevant evidence to the world. Thus, sustainable leadership is a strategic and theological approach to addressing seasonal ministry and strengthening the mission of the church today.